Lipopolysaccharide hyporesponsiveness as a risk factor for intensive care unit hospitalization in infants with respiratory syncitial virus bronchiolitis - Mandelberg, A (Blackwell Science Inc, 2006)
Factors such as genetic heterogeneity in the immune response contribute to respiratory syncytial virus (RSV) bronchiolitis severity. Such heterogeneity may manifest by an aberrant proliferation of phytohaemagglutinin (PHA)-stimulated peripheral blood mononuclear cells (PBMC) in response to lipopolysaccharide (LPS). The proliferation of PBMC was analysed in 52 infants: 21 ambulatory infants with mild RSV bronchiolitis (group I), 26 hospitalized infants with RSV bronchiolitis on ward (group II) and five intensive care unit (ICU) hospitalized infants (group III). Proliferation was analysed in response to negative control, PHA (LPS) and LPS/PHA. The TLR4 mutations were genotyped using reverse-transcriptase–polymerase chain reaction. The optical density (OD) post-LPS/PHA of group II (1·27 ± 0·63) was significantly higher than group II (0·65 ± 0·38, P = 0·005) or group I (0·63 ± 0·33, P = 0·003), suggesting hyporesponsiveness to the LPS attenuation effect. None of the ICU hospitalized infants demonstrated OD readings post-LPS/PHA under the 0·75 threshold as opposed to group I (67% under 0·75) and group II (69%) (P < 0·05). The responses to negative-control, LPS and PHA stimulation alone were similar across groups. The presence of TLR4 mutations (Asp299Gly and Thr399Ile) were associated with severe RSV bronchiolitis and were significantly over-represented in groups II and III. These findings suggest that impairments of PBMC function manifested by hyporesponsiveness to LPS as well as the presence of TLR4 mutations are associated with an increased risk for more severe RSV bronchiolitis in previously healthy infants. A certain threshold of LPS hyporesponsiveness may have a very high negative predictive value for ICU hospitalization, even better than the determination of known TLR4 mutations for this purpose.